Implementasi Program Keluarga Harapan di Kecamatan Karangwareng Kabupaten Cirebon - Anisul Fuad; Deana Nisa Ashriani (UIN Siber Syekh Nurjati Cirebon, 2021)
Poverty is a common terminology that has rubbed against the live broadcast with the condition of nowadays society. Indonesia as a developing country, has an average population living below the poverty line. The Family Hope Program exists as a conditional cash transfer program which aims to accelerate poverty reduction. Where The Family Hope Program seeks to eradicate poverty with various programs in it and focus on the fields of education and health. The implementation of The Family Hope Program in Karangasem Village has been running for almost 13 years after the Ministry of Social Affairs issued a circular in the context of poverty alleviation, namely in 2007. This research aims to determine how the implementation of The Hope Family Program in Karangasem Village. What are the supporting factors and obstacles in the implementation of The Hope Family Program as well as the role of a companion like what is done to the recipients of The Hope Family Program assistance. The research was conducted using a descriptive qualitative method. Data collection techniques using interview methods, observation methhods, and documentation methods. The results of this study stated that in Karangasem Village Dusun 02 the implementation of The Family Hope Program has not been running as is generally done in other villages, many obstacles occurred during the implementation.Â